Influence of nanosilicon on drought tolerance in plants: An overview - Verma, Krishan K.; Song, Xiu-Peng; Singh, Munna; Huang, Hai-Rong; Bhatt, Rajan; Xu, Lin; Kumar, Vinod; Li, Yang-Rui (Frontiers in Plant Science, 2022)
Insufficient availability of water is a major global challenge that plants face and that can cause substantial losses in plant productivity and quality, followed by complete crop failure. Thus, it becomes imperative to improve crop cultivation/production in unsuitable agricultural fields and integrate modern agri-techniques and nanoparticles (NPs)-based approaches to extend appropriate aid to plants to handle adverse environmental variables. Nowadays, NPs are commonly used with biological systems because of their specific physicochemical characteristics, viz., size/dimension, density, and surface properties. The foliar/soil application of nanosilicon (nSi) has been shown to have a positive impact on plants through the regulation of physiological and biochemical responses and the synthesis of specific metabolites. Reactive oxygen species (ROS) are produced in plants in response to drought/water scarcity, which may enhance the ability for adaptation in plants/crops to withstand adverse surroundings. The functions of ROS influenced by nSi and water stress have been assessed widely. However, detailed information about their association with plants and stress is yet to be explored. Our review presents an update on recent developments regarding nSi and water stress in combination with ROS accumulation for sustainable agriculture and an eco-friendly environment.